Azinyl sulfides--CXVIII. Antimicrobial activity of novel 1-methyl-3-thio-4-aminoquinolinium salts - Zieba, A; Wojtyczka, R D; Kepa, M; Idzik, D (Folia microbiologica, 2010)
Synthesis and antimicrobial activity of novel 1-methyl-3-alkylthio-4-aminoquinolinium salts 2 and 1-methyl-3-acylthio-4-aminoquinolinium salts 4 are described. Compounds 2 were obtained by reacting 1-methyl-3,4-(dimethylthio)quinolinium chloride 1 with amines and by reacting 1-methyl-4-aminoquinolinium-3-thiolates 3 with alkylating agents. Compounds 4 were obtained by the reaction of 1-methyl-4-aminoquinolinium-3-thiolates 3 with acylating agents. Antimicrobial activity of compounds 2 and 4 was determined using G+ (Staphylococcus aureus, Enterococcus faecalis) and G(-) (Escherichia coli, Pseudomonas aeruginosa) strains as well as Candida albicans yeast. The compounds show greatest activity against S. aureus whereas the lowest against P. aeruginosa.
Keywords: Candida albicans; Sulfides; sulfidy; aminochinoliny; mikrobiální testy citlivosti; Aminoquinolines; mikrobiální viabilita; Molecular Structure; Gram-Negative Bacteria; antiinfekční látky; Anti-Infective Agents; grampozitivní bakterie; magnetická rezonanční spektroskopie; molekulární struktura; gramnegativní bakterie; Microbial Sensitivity Tests; Microbial Viability; Magnetic Resonance Spectroscopy; Gram-Positive Bacteria